(untitled) (College of Basic Education Research Journal, 2026)
This research examines the catastrophic collapse of Zizon Dam in the Ghab Plain, Hama Governorate, on June 4, 2002, as a case study for analyzing international relief patterns and disaster management mechanisms in Syria prior to 2011. The study employs a documentary-historical methodology grounded in the analysis of reports from the United Nations Office for the Coordination of Humanitarian Affairs (OCHA), which is responsible for organizing and coordinating international emergency responses through ensuring coordination among humanitarian agencies; documents from the United Nations Children’s Fund (UNICEF), which undertakes the protection of children’s rights and provides support in education, health, water, and sanitation sectors during crises; as well as documents from the International Federation of Red Cross and Red Crescent Societies (IFRC), which furnishes technical and logistical assistance to national societies, particularly the Syrian Arab Red Crescent, in addition to reviewing the official institutional narrative disseminated through the Syrian Arab News Agency (SANA) and the associated governmental regulatory discourse .The research commences with an analysis of the engineering-technical background of the dam and an investigation of the cumulative factors leading to its collapse, related to deficiencies in maintenance, modernization, and technical monitoring. It subsequently reviews the initial national response in terms of evacuation, shelter, rescue operations, and aid distribution, while highlighting challenges in early warning systems, communication efficiency, and logistical readiness. The study further examines the role of international actors in coordinating relief and assessing humanitarian needs, whereby OCHA reports contributed to establishing a standardized assessment of the extent of damages, UNICEF focused on water, health, and child protection interventions, while IFRC provided operational support to the Syrian Arab Red Crescent during the emergency response phase. The research addresses the concept of damage assessment as a systematic analytical process aimed at determining the level of material and human losses and estimating actual humanitarian needs, thereby establishing a foundation for the transition to the humanitarian recovery phase, which encompasses infrastructure rehabilitation, restoration of basic services, and livelihood recovery. It also examines the concept of relief documentation as an organizational practice intended to preserve data on assistance and field operations, thereby promoting principles of data governance and institutional transparency .The study concludes with a set of historical and diplomatic lessons pertaining to the dialectic between national sovereignty and international cooperation requirements in managing natural disasters, while emphasizing the importance of enhancing coordination between local and international actors and strengthening early warning systems and integrated risk management frameworks